Ответы и объяснения

  • Участник Знаний
2013-05-27T07:56:07+00:00

( X^4 - 4X^3 + 4X^2) + ( X^2 - 2X + 1) = 1

X^4 - 4X^3 + 4X^2 + X^2 - 2X + 1 - 1 = 0

X^4 - 4X^3 + 5X^2 - 2X = 0

F' = 4X^3 - 12X^2 + 10X - 2 = 0

F" = 12X^2 - 24X + 10 = 0

F" = 2*(6X^2 - 12X + 5) = 0

D = 144 - 4*6*5 = 144 - 120 = 24   V D = 4.8

X1 = 12 + 4.8 \ 12 = 1.4

X2 = 12 - 4.8 \ 12 = 0.6

2013-05-27T08:15:30+00:00

вроде так:

раскрываем скобки и приводим подобные 
x^4-4*x^3+5*x^2-2*x+1 = 1 
x^4-4*x^3+5*x^2-2*x=0 
x*(x-2)*(x-1)^2=0 
х=0 
х=1 
х=2.